Aplikasi Linier Ukuran Tubuh untuk Seleksi Fenotipik Bibit Induk Sapi PO di Kabupaten Bojonegoro (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
The objective of this research was to predict body weight of Peranakan Ongole (PO) cattle using simple linear body measurement. The height wither (HW), body length (BL), heart girth (HG) and chest widht (CW) were measured in centimeters, using caliper, whereas weaning (WW) and yearling weight (YW) was determined in kilograms using a weighing scale. Results of the correlation coefficient showed that hearth girth (HG) highly correlated with body weight was 0.99. In all, the body lenght (HW) had the least correlation coefficient was 0.30 on body weight. Results of the stepwise regression showed that HG was a good estimator of body weight PO cattle. The comparison of residuals indicated that only two equations  accurately predicted body weight. From these results, it was concluded that body weight of Female PO cattle can be estimated using simple linear body measurement of heart girth especially in most remote areas where farmers are challenged with the unavailability of weighing scale